Analiza ustreznosti formatov za dolgoročno hrambo in metapodatkov pri digitalizaciji arhivske kulturne dediščine - Jenuš, Gregor (Moderna arhivistika, 2018)
Digitization of archival records is among the core tasks and processes entrusted to the Slovenian archives by the Slovenian archival legislation. Thus, its role has changed through the decades. Digitization of archival records received a new role. From a process for a long-term preservation of archival cultural heritage, achieved by the conversion of archival records from their analog (physical) form to a digital format that protects original archival records from material damage, to a process that allows a widespread dissemination of it. Archival records become more accessible in existing reading rooms of the Slovenian archival network, as well as in the virtual archival reading room, which is currently under development within the e-ARH.si project. The article deals with changes in the role of digitization, its value in the information-communication society, as well as questions regarding the preparation of archival records for digitization, digitization formats for long-term preservation and associated metadata and their compliance with international standards.
Keywords: analiza; analysis; checklist; digitalizacija; digitization; formati za dolgoročno elektronsko hrambo; formats for long-term electronic preservation; kontrola kvalitete; kontrolni seznam; metadata; metapodatki; quality control